Zwei Räuber. Eine Bemerkung zu Robert Walser und Søren Kierkegaard (Studia theodisca, 2015)
Robert Walser’s robber novel is frequently criticized as an inconsistent and tortuous piece of writing lacking in structure. Moving from these premises, most critics adopt a psychological or psychoanalytic interpretation of this work. My aim is to show that by correlating the main theme of the novel with a motif of Kierkegaard’s Repetition it is possible to better explain what happens in Walser’s text. In this perspective, his novel may be seen as a consequential development of a well-known romantic theme: the mirror theme.